A development of strong and lightweight banpatan red clay body - Punsukumtana, Lada; T.saengchantara, Wanna; Rugthaicharoencheep, Sansanee; Pharaboon, Sasithorn (Bulletin of Applied Sciences, 2022)
This research aimed to develop a lighter weight or lower density red clay body which was used for pottery production in Ban Patan, Sanphakwan district, Chiang Mai province. The body should also have high fired strength, at 1000°C, closed to the body strength used in the current production. The light and strong body would be easier to transport and strong enough to handle. The research was carried out by a selection of raw materials containing organic compounds or porous microstructure. Their chemical elements which could effect on lowering the body temperature had also been considered. The selected raw materials were rice husk, rice hask ash, charcoal, and pulp. Five percents of these raw materials were added into the body and the bodies were fired at 800°C, 900°C, 1000°C. Then the shrinkage, water absorption, density, and bending strength were tested. The study showed that increase the sintering temperature reduced the water absorption but increased shrinkage, density, and bending strength of the body. The additives differently affected the body. The body with rice husk ash or charcoal had higher shrinkage than the red clay or the body with rice husk or pulp. The additives increased the water absorption which pulp gave higher value than rice hash, rice husk ash, and charcoal. As a result, the density changed as the following order: rice husk and pulp < charcoal <rice hask. The strength changed as the following order: charcoal> rice husk, pulp, and red clay > rice hask ash. When comparing the strength at the same density, it was found that the charcoal addition provided the maximum bending strength. In conclusion, five percent charcoal adding into the red clay, Ban Patan, Sanphakwan district, Chiang Mai province, fired at 1000°C caused a decrease in density but an increase in bending strength which resulted in light and strong red clay body to enable easier handling.